Draft Implementation Learning Discovery Learning Interpretation Material Through Artificial Intelligence Chatbot Media Era Society 5.0 - Takrip, Muhamad; Pathurrahman, Pathurrahman; Supriyanto, Jhon; Nadhiran, Hedhri; Almunadi, Almunadi; Halimatussa'diyah, Halimatussa'diyah (Proceeding International Conference on Religion, Science and Education, 2025)
Learning interpretation material that is still monotonous, participants educate only circles certain No all participant educate wish learn, and they not enough understand what is taught. This is happen Because participant educate experience difficulty in understand interpretation material taught by the teacher, and reduce interest they in learning, which has an impact on the results Study they . Discovery Learning is one of them effort For increase interest learning and Chatbot is one of types of AI that can teach user with ability learning machine interactive. The goal increase interest learn interpretation and more interesting For combining the virtual world and the real world as method For do innovation in learning Islamic religious education . Focus study This is qualitative with analyze problem related innovation learning interpretation material. Research This use study literature and concentrate on the ideas, benefits , and barriers associated with it. with use of AI chatbots for learning direct interpretation material . Research result show that approach Islamic religious education in general directly using AI chatbots in the digital era has very potential big . Learning This No only fun, but also can be help development they in a way overall . This own Lots benefits , such as increase Power pull learning , enabling approach more individual learning , and provide effective support For fulfil need specific to the Society 5.0 era.